2015
DOI: 10.1186/s13054-015-0759-2
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the inspiratory time and I:E ratio during mechanical ventilation aggravates ventilator-induced lung injury in mice

Abstract: IntroductionLung-protective ventilation reduced acute respiratory distress syndrome (ARDS) mortality. To minimize ventilator-induced lung injury (VILI), tidal volume is limited, high plateau pressures are avoided, and positive end-expiratory pressure (PEEP) is applied. However, the impact of specific ventilatory patterns on VILI is not well defined. Increasing inspiratory time and thereby the inspiratory/expiratory ratio (I:E ratio) may improve oxygenation, but may also be harmful as the absolute stress and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 32 publications
1
29
0
Order By: Relevance
“…However, an increased I : E ratio yields the risk of incomplete expiration 17 and is suspected of aggravating ventilator-induced lung injury. 18 EVA ventilation, however, is based on direct measurement of P trach and switches from inspiration to expiration if PIP is achieved and from expiration to inspiration if PEEP is achieved. Thus, by its mere controlling principle, incomplete expiration or negative pressure development should be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…However, an increased I : E ratio yields the risk of incomplete expiration 17 and is suspected of aggravating ventilator-induced lung injury. 18 EVA ventilation, however, is based on direct measurement of P trach and switches from inspiration to expiration if PIP is achieved and from expiration to inspiration if PEEP is achieved. Thus, by its mere controlling principle, incomplete expiration or negative pressure development should be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…It was believed previously that the immunomodulatory diet could suppress the elevated inflammatory reactions during ALI/ARDS [ 5 ], and patients could benefit from it [ 6 ]. Preclinical studies reported that Omega-3 (EPA and DHA) could reduce leukotriene synthesis and the production of prostaglandin E2, which could be beneficial in ALI/ARDS [ 3 , 11 , 13 ]. The antioxidants could also reduce the inflammation through scavenging free radicals [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is mainly caused by predisposing disorders such as pneumonia, aspiration, shock, and severe sepsis [ 2 ]. Benefiting from the exploration of the pathophysiology of ALI/ARDS, we know that after having been affected by these diseases, neutrophils will infiltrate into the alveolar space and pulmonary mesenchyme, where they will release pro-inflammatory cytokines and eventually cause ALI/ARDS [ 2 ], which is characteristic of leakage of edema fluid and mismatch of ventilation and perfusion [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, in mouse experiments with high TV ventilation, lung injury was induced more with the IRV than by conventional mechanical ventilation. 27 During intense exercise, the O 2 demand increases beyond the limit of pulmonary diffusion capacity, thus increasing the alveolar-arterial oxygen difference and inducing hypoxemia. 28 It was shown that the heart rate increases to 145-180/min during a marathon.…”
Section: Discussionmentioning
confidence: 99%